RNA Coronaviruses’ Outbreaks: Recent Progress on the SARS-CoV-2 Pandemic Diagnostic Tests, Vaccination and Therapeutics - Suaifan, Ghadeer A.R.Y.; Alkhawaja, Bayan A.; Mohammed, Aya A.M. (Mini Reviews in Medicinal Chemistry, 2022)
Coronaviruses are RNA-infective viruses that could be considered principal players in universal high-profile outbreaks, namely the Severe Acute Respiratory Syndrome (SARS, 2002-2003), the Middle East Respiratory Syndrome (MERS, 2012) and the continuing novel coronavirus disease (COVID-19, 2019) pandemic. RNA coronaviruses infections raise public health concerns with infections’ severity ranging from serious pandemics and highly contagious infections to common influenza episodes. With a wide consensus concerning the seminal role of early detection of the infectious agent on the clinical prognosis, recent technological endeavors have facilitated the rapid, sensitive and specific diagnosis of viral infections. Given that the burst of confirmed cases of the novel coronavirus disease 2019 (COVID-19) are climbing steeply, and we are amid this pandemic, this work will center at the respiratory RNA-viruses outbreaks, including the three coronaviruses-related pandemics, emphasizing on the approved diagnostic approaches, outlining therapeutic clinical trials as well as vaccine candidates. Based on the accumulated data and knowledge on the previous RNA-virus outbreaks, this review aspires to link the current intervention measures against SARS-CoV-2 infection with the previous interventions and to provide a roadmap for any possible future measures.
Keywords: vaccines